Trends in Project-Based Learning Implementation in Science Education (2015-2025): A Systematic Literature Review - Kharisma Sulistya Akhmadi; Heru Kuswanto; Sul Daeng Naba (Universitas Lambung Mangkurat, 2026)
The paramount goal of this study was to meticulously identify and critically analyze contemporary trends regarding the integration of the Project-Based Learning (PjBL) pedagogical model within science education settings. The adopted research strategy was a Systematic Literature Review (SLR), strictly adhering to the PRISMA framework guidelines, with rigorously defined inclusion and exclusion criteria. The literature sources for this review were exclusively focused on national journals indexed in the Science and Technology Index (SINTA), specifically tiers SINTA 2, SINTA 3, and SINTA 4. The search utilized core keywords encompassing the